Antibacterial validation of electrogenerated hypochlorite using carbon‐based electrodes. (26th September 2014) - Locker, J.; Fitzgerald, P.; Sharp, D.
Abstract This proof‐of‐concept study explores the novel use of carbon‐based electrodes for the electrochemical generation of hypochlorite and compares the antimicrobial efficacy against commercial hypochlorite solution. Antimicrobial concentrations of hypochlorite were generated using pad‐printed carbon and carbon fibre electrodes, yielding up to 0·027% hypochlorite in 60 min and 0·1% hypochlorite in 15 min, respectively, in a nondivided assembly. The minimum inhibitory concentration (MIC) of the electrogenerated hypochlorite produced using carbon fibre electrodes was established for four medically important bacteria (Pseudomonas aeruginosa and Staphylococcus aureus approx. 0·025%, Escherichia coli and Enterococcus faecalis approx. 0·012%) and found to be in agreement with those determined using commercial hypochlorite solution. Therefore, carbon‐based electrodes, particularly carbon fibre, have proven effective for the generation of antimicrobial concentrations of hypochlorite. The similarity of the MIC values to commercial hypochlorite solutions suggests that the antimicrobial efficacy is derived from the quantified hypochlorite generated and not due to marked cogeneration of reactive oxygen species, as identified for other assemblies. As such, the application of carbon electrodes may be suitable for the local production of hypochlorite for healthcare antisepsis. Significance and Impact of the Study Carbon fibre electrodes can rapidly generate antimicrobial concentrations of hypochlorite; as such, these cheap and commercially available electrodes are proposed for the local production of hypochlorite for healthcare antisepsis. Importantly, the antimicrobial properties of the electrochemically generated hypochlorite mirror those of commercial hypochlorite, suggesting this is not enhanced by the cogeneration of reactive oxygen species. This illustrates the potential use of disposable carbon electrodes for localized small‐volume production of hypochlorite for surface and skin cleansing, and opens a broader scope of research into the exploitation of carbon electrodes for this application.